THE ANALYSIS OF LAND CARRYING CAPACITY AND NON BEHAVIOURAL CAUSES EFFECTS TO FARMER’S BEHAVIOUR ON WET LAND CONSERVATIONS IN KULON PROGO REGENCY - Dian Kurniasih (Widyariset, 2013)
The research aimed to analyze: (1) the level of farmers behaviour on wet land conservations in Kulon Progo Regency; (2) the impact of land carrying capacity and non behavioural causes to farmers behaviour on wet land conservations; (3) the impact of farmers behaviour on wet land conservations of their agribusiness income. The method used in this study was descriptive analysis. The research was done in Kulon Progo Regency. The location chosen by purposive sampling method represented area that have high or low level of land carrying capacity. The respondents were chosen by multistage random sampling method. The analysis methods used in this research are proportion test by Dajan, multiple linear regression analysis, and simple linear regression analysis. The results indicated that more than 50% farmers in Kulon Progo Regency have a high level of conservations behaviour. The level of land carrying capacity did not influence farmers behaviour on wet land conservations. Non behavioural causes influenced the farmers behaviour on wet land conservations significantly were age, conservation knowledge, motivation, activity in group, non agribusiness income, availability of organics input and leadership. The high level of farmer’s behaviour on wet land conservations did not influence their agribusiness income.